The Making of the Rabbi-Scholar in Late Ancient Palestine: Torah Study and Its Others in the Yerushalmi - Vidas, Moulie (Harvard theological review, 2025)
This article identifies a development in rabbinic discourse about Torah study. Whereas early texts contrast study with activities like earning a living, the Palestinian Talmud presents a new debate in which study stands in binary opposition to activities otherwise considered part of the life of Torah, such as good deeds and prayer. This debate shaped the eventually dominant view of the rabbinic sage as primarily, or even exclusively, a scholarly figure. The article shows how this discourse was formulated through adaptation of earlier sources and considers how it may have responded to broader transformations in the sages’ world.